SCHIZOPHRENIC EXPERIENCES IN PIGPEN WEBTOON: PSYCHOANALYTIC LITERARY CRITICISM - Nur Shaffirah Anuar; Hidayati, Hidayati; Bima Prana Chitra (Jurnal Pendidikan dan Sastra Inggris, 2022)
This research discusses about the main character’s state of mind in Pigpen webtoon through the approach of psychoanalysis in literary criticism. This research aims to analyze the types of schizophrenic experiences and desires that are reflected in the main character’s schizophrenia by using the theory of schizophrenia and Jacque Lacan’s psychoanalysis. The methodology applied in this research is the qualitative research method to elaborate on the phenomena of psychology in literary works. This analysis is supported by the data acquired from journals, books, theses, and Pigpen webtoon as the data source. The writer identifies several results from the analysis that has been done that are relevant to the idea psychology approach. First, from the theory of schizophrenia, the main character is mainly going through delusions and hallucinations. Second, through Lacan’s psychological concept of desire and identity formation, the writer found two desires in the main character: the desire to have (anaclitic desire) and the desire to be (narcissistic desire), which happened in the Imaginary and Symbolic stages. In relation to desires, it is found that the main character’s experiences of schizophrenia are influenced by his desires. The schizophrenic experiences reflected forms of the main character’s desires for fulfilment.